2020
DOI: 10.18632/aging.202193
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of COVID-19 in patients with autoimmune rheumatic diseases

Abstract: The characteristics of COVID-19 patients with autoimmune rheumatic diseases (AIRD) have rarely been reported. Patients with AIRD have suppressed immune defense function, which may increase their susceptibility to COVID-19. However, the immunosuppressive agents AIRD patients routinely used may be beneficial for protecting the cytokine storm caused by SARS-CoV-2. In this retrospective study, we included all confirmed cases in Huoshenshan Hospital from February 4 to April 9. Data were extracted from electronic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Conversely, TNFi appeared to have a protective role being associated with a reduction of the development of a more severe COVID-19 [64]. Finally, other small case series were available furtherly confirming these findings, as described in Table 1 [65,66].…”
Section: Incidence and Outcomes Of Covid-19 In Arthritis Patientssupporting
confidence: 57%
“…Conversely, TNFi appeared to have a protective role being associated with a reduction of the development of a more severe COVID-19 [64]. Finally, other small case series were available furtherly confirming these findings, as described in Table 1 [65,66].…”
Section: Incidence and Outcomes Of Covid-19 In Arthritis Patientssupporting
confidence: 57%
“…Several studies that have focused on the COVID-19 outcomes in patients with RMD have shown mixed results. While some studies have shown no difference in outcomes of COVID-19 among those with RMDs as compared to the general population [ [5] , [6] , [7] ], a few others have shown contradicting results [ 8 , 9 ]. The reasons for such diverse results may be numerous, ranging from the geographical location, the genetic make-up of the study population, prevalence of comorbidities, immunosuppressive agent usage, and, most importantly, the heterogeneity between different RMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Tan C et al found that the significant increase of C-reactive protein (CRP) may be a potential early predictor for the severity of COVID-19, for CRP changes precede the imaging findings ( 65 ). And cohort studies reported a significant correlation between poor prognosis and elevated serum ferritin, IL-6 and procalcitonin ( 15 , 66 , 67 ). In their meta-analysis, Hariyanto et al ( 68 ) summarized the predictive roles of increased procalcitonin (≥0.065 ng/ml), CRP (≥33.55 mg/L), D-dimer (≥0.635 μg/L), LDH (≥263.5 U/L) and decreased albumin (≤38.85 g/L) in the clinical prognosis of COVID-19 ( 68 ).…”
Section: Applicable Laboratory Indicatorsmentioning
confidence: 99%
“…However, studies have also shown that the diagnostic rate of SARS-CoV-2 in RADs patients does not necessarily increase, at least, they are less likely to develop into severe cases (13,14). By analyzing the 2-month electronic medical records of Huoshenshan Hospital in Wuhan, China, a study showed the admission rate of ICU, hospital stays and mortality of COVID-19 in RADs patients were similar to the non-RADs patients (15), and these points have been supported by other cohort studies (16)(17)(18). It has even been reported that the prevalence of COVID-19 in RADs patients is lower than that of randomly selected non-RADs patients (19), which is based on the explanation that RADs patients are more consciously following the rules of epidemic prevention and control.…”
Section: Table 1 |mentioning
confidence: 99%
See 1 more Smart Citation